2000
DOI: 10.1080/13625180008500402
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age, body mass index, smoking and general health on the risk of venous thromboembolism in users of combined oral contraceptives

Abstract: We believe that, before prescribing combined oral contraceptives, the venous as well as the arterial factors need to be considered and, in addition, age, obesity and smoking are all relevant when assessing an individual patient's risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 17 publications
(16 reference statements)
1
42
0
3
Order By: Relevance
“…Obesity is a well-known risk factor of VTE [Nightingale et al 2000;Bergendahl et al 2012] and the increase in risk is about threefold. This increase is approximately of the same magnitude in COC users.…”
Section: Acquired Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a well-known risk factor of VTE [Nightingale et al 2000;Bergendahl et al 2012] and the increase in risk is about threefold. This increase is approximately of the same magnitude in COC users.…”
Section: Acquired Risk Factorsmentioning
confidence: 99%
“…The risk of VTE increases with age [Nightingale et al 2000;Bergendahl et al 2012]. A healthy, normal weight woman can be prescribed COC also during the ages 40-49 years but other potential risk factors must always be evaluated in relation to the age of the individual.…”
Section: Acquired Risk Factorsmentioning
confidence: 99%
“…Six studies investigated patients Ͻ55 years of age. 12,36,40,41,43,50 Four of the studies involved only patients Ͼ45 years of age. 1,7,37,48 The mean age of the other studies ranged between 42 and 70 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…11,13,38,39,42,44 -47,49 As far as sex was concerned, 8 studies investigated only women, 13,36,39 -41,43,48,50 5 of these in the range of 15 to 50 years of age. 36,40,41,43,50 In 3 studies, only men were included. 7,12,37 All 4 cohort studies were prospective, 1,7,48,49 with a duration of follow-up between 5.6 48 and 26 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…CHCs contain both estrogen and a progestin and include combined oral contraceptives (COCs), the combined contraceptive vaginal ring and the combined transdermal contraceptive patch. Observational studies and meta-analyses have reported elevated risks of coronary heart disease, myocardial infarction (MI), stroke, venous thromboembolism (VTE) and peripheral arterial disease (PAD) among women who smoke and use CHCs [18][19][20][21][22][23][24][25][26][27][28][29]. The mechanisms underlying increased CVD risk in female smokers who use CHCs are poorly understood but could include effects of products of combustion, nicotine exposure or both.…”
Section: Introductionmentioning
confidence: 99%